Molecular insights into DNA interference by CRISPR-associated nuclease-helicase Cas3 - Gong, Bei; Shin, Minsang; Sun, Jiali; Jung, Che-Hun; Bolt, Edward L.; van der Oost, John; Kim, Jeong-Sun (Proceedings of the National Academy of Sciences - PNAS, 2014)
Significance Bacteria can repel invader DNA and RNA molecules by using an adaptive immunity mechanism called clustered regularly interspaced short palindromic repeats (CRISPRs)-Cas. CRISPR loci in a host genome are a repository of DNA fragments obtained from previous encounters with an invader, which can be transcribed and activated into short RNA molecules (crRNA) with sequences complementary to invader DNA or RNA. In some CRISPR-Cas systems, crRNA is assembled into a targeting complex called “Cascade” that seeks invader DNA to form an R-loop that triggers recruitment of a nuclease-helicase, Cas3, to destroy invader DNA. In this study, we show atomic resolution structures of a full-length Cas3, revealing how Cas3 coordinates binding, ATP-dependent translocation, and nuclease digestion of invader DNA. Mobile genetic elements in bacteria are neutralized by a system based on clustered regularly interspaced short palindromic repeats (CRISPRs) and CRISPR-associated (Cas) proteins. Type I CRISPR-Cas systems use a “Cascade” ribonucleoprotein complex to guide RNA specifically to complementary sequence in invader double-stranded DNA (dsDNA), a process called “interference.” After target recognition by Cascade, formation of an R-loop triggers recruitment of a Cas3 nuclease-helicase, completing the interference process by destroying the invader dsDNA. To elucidate the molecular mechanism of CRISPR interference, we analyzed crystal structures of Cas3 from the bacterium Thermobaculum terrenum , with and without a bound ATP analog. The structures reveal a histidine-aspartate (HD)-type nuclease domain fused to superfamily-2 (SF2) helicase domains and a distinct C-terminal domain. Binding of ATP analog at the interface of the SF2 helicase RecA-like domains rearranges a motif V with implications for the enzyme mechanism. The HD-nucleolytic site contains two metal ions that are positioned at the end of a proposed nucleic acid-binding tunnel running through the SF2 helicase structure. This structural alignment suggests a mechanism for 3′ to 5′ nucleolytic processing of the displaced strand of invader DNA that is coordinated with ATP-dependent 3′ to 5′ translocation of Cas3 along DNA. In agreement with biochemical studies, the presented Cas3 structures reveal important mechanistic details on the neutralization of genetic invaders by type I CRISPR-Cas systems.